Fourth World Congress of Jewish Studies in Jerusalem (July 25 – Aug. 1) 1965 - Hallo, William W.
espec. H. Tadmor on native Mesopotamian antecedents to Assyrian historiography; A. Malamat on the bearing of the latest Mari evidence on the origins of Biblical prophecy (cf. 29:959; 29:960; 29:961)'; W. W. Hallo (29:357 =); A. Shaffer on a parallel between a Sumerian Gilgamesh episode and Eccl. 4: 9-12 (= 29:220); Biblical lexicography in the light of Ugaritic: A. M. Honeyman, M. Held, M. Sznycer.